Manipulasi Lokasi Driver Shopee Food Perspektif Maqāṣid Asy-Syarī’ah dan Sosiologi Hukum - Nur Mifchan Solichin; Diah Nuraini; Fakhrozi Afif (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to analyze the use of the Fake GPS application by Shopee Food drivers in Ambarawa District from the perspective of Maqāṣid Ash-Sharī'ah and Legal Sociology. The research method used is field research with a descriptive qualitative approach. The research subjects were Fake GPS user and non-user drivers, marketplace owners, and consumers. Data were collected through in-depth interviews, observation, and documentation. The theory used is Maqāṣid Asy-Sharī'ah (Haroen, 1996) to assess the suitability of this practice with the principles of justice and Islamic values, and the theory of Legal Sociology (Rahardjo, 1982) to understand the relationship between law and social reality. The results show that the practice of using Fake GPS is driven by economic pressure, the Shopee Food bonus system, and the tight competition between drivers. From the perspective of Maqāṣid Ash-Sharī'ah, this action harms the values of Hifz ad-Din, Hifz an-Nafs, Hifz al-Mal, and Hifz al-Aql because it triggers dishonesty, potential harm, economic injustice, and cheating habits. From a Sociology of Law perspective, this phenomenon shows a mismatch between the ideal norms of Shopee Food and the social conditions of the drivers. This research recommends religious value education, revision of order algorithms, humanist law enforcement, economic empowerment of drivers, and dialog forums so that solutions are more holistic and according to local needs.